Dose-Dependent Association Between Pancasila Student Profile (P5) Curriculum Exposure and Civic Engagement Among Indonesian Secondary School Students - Arya Ganendra; Delia Tamim (Enigma Institute, 2026)
The Projek Penguatan Profil Pelajar Pancasila (P5; Pancasila Student Profile Strengthening Project), a defining component of Indonesia’s Kurikulum Merdeka introduced in 2022, was designed to cultivate civic values and participatory dispositions among secondary students through interdisciplinary, project-based learning, yet large-scale quantitative evidence on its association with measurable civic engagement remains scarce. This cross-sectional study evaluated the association between P5 exposure intensity and civic engagement among Indonesian secondary school adolescents, controlling for established sociodemographic confounders. A stratified cluster sample of 312 students (Grades 10–12) was recruited from 18 public and private, urban and rural secondary schools across five Indonesian provinces. Civic engagement was measured with a 25-item instrument adapted from the IEA International Civic and Citizenship Education Study framework (Cronbach’s α = 0.84; composite 0–100; high engagement ≥ 65). P5 exposure was classified as high, moderate, or low from school-level participation scores. Multivariable binary logistic regression identified independent predictors of high civic engagement. Civic-engagement scores increased monotonically across exposure groups (low 49.1, moderate 61.0, high 72.3; ANOVA F(2,309) = 86.85, p < 0.001; η² = 0.36; Cohen’s d = 2.04 for high vs low). High P5 exposure was independently associated with markedly increased odds of high civic engagement (adjusted OR = 17.12; 95% CI 3.82–76.74; p < 0.001), as was each unit of continuous participation (OR = 2.44; 95% CI 1.71–3.48; p < 0.001); the model showed good fit (AUC = 0.82; Nagelkerke R² = 0.41). In conclusion, these findings provide early large-scale quantitative evidence that P5 exposure is robustly associated with stronger civic engagement, supporting high-fidelity, equitable national implementation of the Merdeka Curriculum.